Extracellular vesicles of the probiotic bacteria E. coli O83 activate innate immunity and prevent allergy in mice - Schmid, Anna Marlene; Razim, Agnieszka; Wysmołek, Magdalena; Kerekes, Daniela; Haunstetter, Melissa; Kohl, Paul; Brazhnikov, Georgii; Geissler, Nora; Thaler, Michael; Krčmářová, Eliška; Šindelář, Martin; Weinmayer, Tamara; et al. (Cell communication and signaling, 2023)
BACKGROUND: E. coli O83 (Colinfant Newborn) is a Gram-negative (G-) probiotic bacterium used in the clinic. When administered orally, it reduces allergic sensitisation but not allergic asthma. Intranasal administration offers a non-invasive and convenient delivery method. This route bypasses the gastrointestinal tract and provides direct access to the airways, which are the target of asthma prevention. G- bacteria such as E. coli O83 release outer membrane vesicles (OMVs) to communicate with the environment. Here we investigate whether intranasally administered E. coli O83 OMVs (EcO83-OMVs) can reduce allergic airway inflammation in mice. METHODS: EcO83-OMVs were isolated by ultracentrifugation and characterised their number, morphology (shape and size), composition (proteins and lipopolysaccharide; LPS), recognition by innate receptors (using transfected HEK293 cells) and immunomodulatory potential (in naïve splenocytes and bone marrow-derived dendritic cells; BMDCs). Their allergy-preventive effect was investigated in a mouse model of ovalbumin-induced allergic airway inflammation. RESULTS: EcO83-OMVs are spherical nanoparticles with a size of about 110 nm. They contain LPS and protein cargo. We identified a total of 1120 proteins, 136 of which were enriched in OMVs compared to parent bacteria. Proteins from the flagellum dominated. OMVs activated the pattern recognition receptors TLR2/4/5 as well as NOD1 and NOD2. EcO83-OMVs induced the production of pro- and anti-inflammatory cytokines in splenocytes and BMDCs. Intranasal administration of EcO83-OMVs inhibited airway hyperresponsiveness, and decreased airway eosinophilia, Th2 cytokine production and mucus secretion. CONCLUSIONS: We demonstrate for the first time that intranasally administered OMVs from probiotic G- bacteria have an anti-allergic effect. Our study highlights the advantages of OMVs as a safe platform for the prophylactic treatment of allergy. Video Abstract.
Keywords: přirozená imunita; Allergic airway inflammation; extracelulární vezikuly; Lipopolysaccharides; Inflammation; HEK293 buňky; probiotika; lipopolysacharidy; Outer membrane vesicles; HEK293 Cells; Escherichia coli; Nasal route of administration; alergie; Immunity, Innate; zánět; Extracellular Vesicles; Animals; lidé; Humans; zvířata; myši; Probiotics; Microbiota and innate immunity; Asthma; Mice; Extracellular vesicles; Hypersensitivity; bronchiální astma